PENERAPAN RASIONALITAS EKONOMI ISLAM DALAM MENGENDALIKAN PERILAKU ISRAF DI TENGAH PANDEMI - Andri Awaluddin (Jurnal Ilmu Akuntansi dan Bisnis Syariah (AKSY), 2021)
Human beings as social beings in an effort to meet the needs of their lives are always doing economic activities. To regulate these economic activities, there are several economic systems that can be applied, some that adhere to the capitalist economic system, some that adhere to the social economic system. But as Muslims should impose an economic system can put the interests of the people above personal interests so as to create rationality in conducting economic activities. As a human being who has lust tends to have excessive consumption behavior (israf), but man also has a sense that is able to control consumptive nature so that in fulfilling the needs of his life man always control himself to be free from israf behavior.  In the making of this journal the author uses qualitative research methods with literature research. Keywords: Rationality, Islamic Economy, Israf